A Hitchiker 's guide to digital social innovation - Loretta Anania; Antonella Passani (International Telecommunications Society (ITS), 2014)
Social innovation plays an important role in addressing societal challenges. We map Digital Social Innovation (DSI) in terms of the international research efforts and investments made in Europe over the last decade. DSI aims to promote innovation and social change based on the network effect: meaning internet connections, web collaborative tools, sharing of open data and a process of bottom-up peer-supported activities and applications). Examples are given on the novel use of information platforms, data from sensor networks and community use of mobile phones. The impact measurement of the DSI initiative at social, economic and environmental level is presented. Our data comes from the EU activities and R&D grants awarded up to 2014. We describe the concept, the context, and the type of investments made by the European Union in this field. The final part of the paper concerns DSI impact evaluation and proposes a methodological framework for assessing specific results in a qualitative and quantitative way.
Keywords: 330